(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2024)
The retail business is always changing, and with it, conventional practices & customer expectations. The emergence of digital transformation is adding new dimensions to this complexity. The significant effects of digital transformation on retail management techniques & consumer behaviours are the subject of this study. Globalisation & technological advancements are driving these shifts since they shape the reality of today’s consumers and define many corporate operations. Consumers are evolving in terms of their wants, needs, values, lifestyle choices, & the products and services they purchase as a result of digitalization’s pervasive influence on every facet of public life. Presenting the influence of digitisation on customer behaviour in retail is the purpose of the essay. As a result, we will look at digitalisation in the broadest sense, ignoring particular types, and at the changes in consumer behaviour as a whole, omitting any mention of particular shifts. There is a focus on retail, changing consumer behaviours, and new technology as part of the study process.